Vestibular Rehabilitation and Factors That Can Affect Outcome - Whitney, Susan L.; Sparto, Patrick J.; Furman, Joseph M. (Seminars in Neurology, 2020)
This review will discuss the developmental, environmental, medical, psychological, visual, and other sensory-related factors that affect recovery after vestibular dysfunction. A general overview of the evidence for vestibular rehabilitation for patients with peripheral and central vestibular disorders is provided. Recent findings suggest that age, physical activity, certain congenital disorders, length of symptoms, musculoskeletal, visual and neuromuscular comorbidities, cognition, sleep, and medications are all factors that influence the effectiveness and outcome of vestibular rehabilitation. Psychological factors that also affect outcome include anxiety, depression, fear of movement, and fear of falling. Recovery in patients with vestibular disorders may be enhanced if the practitioner recognizes and attempts to remediate modifiable factors.
Keywords: vestibular rehabilitation; vestibular physiotherapy; physical therapy; prognosis; dizziness; vertigo